(3JMdjd GdNWGH GdEYdGej CWQ fXQjI h feGPL JWHjbjI (B/s - (3TheGf, eMeOs ((3GdbGgQI (B:s (3GdOGQ GdeUQjI GddHfGfjI ,s, 2012)
(3GdJMdjd GdSjejhdhLj h GdJMdjd GdKbGaj h GdJMdjd GdGLJeGYj GdGOQGcj h GdJMdjd GdfbOj Ke jJfGhd edGeM GdeOQSI GdGdGeGfjI aj JMdjd GdNWGH GdGYdGej Ke jNJJe GdcJGH HJfGhd eeGQSGJ h feGPL JWHjbjI dPdc GdJMdjds
(3HHdjhZQGajG (B: (3U(B.168-176s
Keywords: (3GdNWGH GdEYdGejs; (3GdJMdjd GdfbOjs; (3GdNWGHs